Household income analysis of Miag-ao, Iloilo town proper - Alolosan, Gene J
The objective of the study is to evaluate the household income of Miag-ao Town Proper. Specifically, it aims to develop economic and demographic profiles of the households and their respective household incomes. It would like also to determine the household income distribution of town proper, and compare it with the national and regional distribution of income. Lastly, it aims determine the level of inequality that persists in the said locality, and compare it with the national, regional, and provincial level of inequality. The data analyzed in this study were obtained by conducting guided-interviews with 167 household heads. The instrument was based on the Family Income and Expenditure Survey (FIES) of the NSO. It was found out that the average household size in the area is with 6 members. Households are mostly composed of single families. The registered average annual income earned by each household is P358,713 while the median income was P194,456. Most of the incomes were derived from wages and salaries from employment. The income distribution of the area is heavily skewed to the right. The richest ten percent obtained nearly half of the total income while the bottom 10 percent yielded only 0.58 percent. The lower half of the deciles received only nearly 10 percent while almost 90 percent of the income was accrued by the upper 50 percent of the total samples. The resulted value of the Gini ratio is .5842which is higher than the national, regional, and provincial ratios. The paper concluded that the level of inequality that persists in a specific area does not necessarily pattern the level of inequality in the national or regional level. It was recommended that the local government unit of the area should frame programs and policies providing livelihoods to households belonging to lower deciles that would result to the redistribution of income.